Glass fiber reinforced polypropylene composition

By developing a glass fiber reinforced polypropylene-based composition containing specific components and structures, the shortcomings of existing materials in tensile properties and soft touch are solved, and the combined effects of high fracture strain, tensile strength and soft touch are achieved. , meets the high requirements for interior components in the automotive industry.

CN119452000APending Publication Date: 2025-02-14北欧化工公司
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202380048892.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-01
Filing Date
2023-06-29
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The fracture strain of existing glass fiber reinforced materials in tensile tests is not sufficient to meet high demands, while the automotive industry has increased material demand for interior parts with soft touch, and the recirculation complexity of leather-polymer composites Increased demand for alternative materials.

Method used

A glass fiber reinforced polypropylene-based composition was developed, containing 40-55% propylene-1-butene random copolymer or ethylene-propylene random copolymer and 20-40% high pressure polyethylene acrylate copolymer. , 10-30% short glass fiber, 0.5-2.5% coupling agent and 0.05-0.9% slip agent, by optimizing the composition and structure of the composition, its tensile properties and soft touch feel are improved.

Benefits of technology

It has achieved the improvement of the fracture strain and tensile strength of glass fiber reinforced materials, and has a soft touch feeling, which can replace leather-polymer composite materials and meet the high requirements of the automotive industry for interior components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005201069440000061
    Figure BDA0005201069440000061
  • Figure BDA0005201069440000121
    Figure BDA0005201069440000121
  • Figure BDA0005201069440000131
    Figure BDA0005201069440000131
Patent Text Reader

Abstract

The glass fiber reinforced polypropylene-based composition comprises a propylene-1-butene random copolymer or an ethylene-propylene random copolymer, a high-pressure polyethylene acrylate copolymer and short glass fibers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to glass fiber reinforced materials suitable for applications with high demands on tensile and elongation properties. Background Art

[0002] A fiber-reinforced composition is known from EP 3 105 287, which comprises a metallocene-derived random copolymer of polypropylene and glass fibers and an adhesion promoter. However, the strain at break (%) in the tensile test is insufficient for demanding applications. Furthermore, there has long been a need in the automotive industry, in particular, for compositions suitable for interior parts with an extremely soft touch. Today, interior parts for premium passenger cars are evaluated entirely by their touch, with customers tending to demand a leather-like touch and at the same time also the stiffness conventionally foreseen for such articles. This goal is even more important since leather-polymer composites make recycling more complicated. Summary of the invention

[0003] The present invention provides a glass fiber reinforced polypropylene-based composition, wherein the melt flow rate (ISO 1133, 2.16 kg; 230° C.) of the glass fiber reinforced polypropylene-based composition is 1.0 to 50 g / 10 min, and the glass fiber reinforced polypropylene-based composition comprises:

[0004] a) 40 to 55% by weight of a propylene-1-butene random copolymer or an ethylene-propylene random copolymer, wherein the propylene-1-butene random copolymer or the ethylene-propylene random copolymer has:

[0005] aa) a melting temperature of 135 to 150° C. (DSC; ISO 11357-3);

[0006] ab) a content of units derived from 1-butene of 3.0 to 9.0% by weight or a content of units derived from ethylene of 2.0 to 6.0% by weight (determined by NMR spectroscopy);

[0007] ac) a melt flow rate MFR2 (ISO 1133, 2.16 kg; 230° C.) of 8.0 to 120 g / 10 min;

[0008] b) 20 to 40% by weight of a high-pressure polyethylene acrylate copolymer, wherein the density of the high-pressure polyethylene acrylate copolymer is 910 to 935 kg / m 3 , the high pressure polyethylene acrylate copolymer optionally contains units derived from vinyltrimethoxysilane;

[0009] c) 10 to 30% by weight of short glass fibers;

[0010] d) 0.5 to 2.5 wt % of a coupling agent;

[0011] All amounts are relative to the total weight of the glass fiber reinforced polypropylene based composition.

[0012] The present invention also provides an article comprising the glass fiber reinforced polypropylene-based composition.

[0013] The present invention also relates to the use of glass fiber reinforced polypropylene based compositions for replacing leather-polymer composite materials.

[0014] It goes without saying, because the density is 910 to 935 kg / m 3 The melting points of the high pressure polyethylene acrylate copolymers optionally containing units derived from vinyltrimethoxysilane do not overlap substantially, so the melting points of the propylene-1-butene random copolymer or the ethylene-propylene random copolymer can be measured in an all-glass fiber reinforced polypropylene based composition.

[0015] The propylene random copolymer contained in the glass fiber reinforced polypropylene-based composition of the present invention may be a propylene-1-butene random copolymer in the first embodiment or an ethylene-propylene random copolymer in the second embodiment. The first embodiment, ie, a propylene-1-butene copolymer, is preferred due to better rigidity.

[0016] The glass fiber reinforced polypropylene-based composition described herein preferably comprises 0.05 to 0.9 wt% of a slip agent relative to the total weight of the glass fiber reinforced polypropylene-based composition. More preferably, the slip agent is wax-containing erucamide.

[0017] In another independently preferred aspect, the high pressure polyethylene acrylate copolymer comprises units derived from butyl acrylate.

[0018] The glass fiber reinforced polypropylene-based composition of the present invention more preferably comprises a high-pressure polyethylene acrylate copolymer containing units derived from vinyltrimethoxysilane.

[0019] Even more preferably, the glass fiber reinforced polypropylene-based composition comprises a high pressure polyethylene acrylate copolymer, the high pressure polyethylene acrylate copolymer comprising:

[0020] a) 7.0 to 12.0 wt. % of units derived from butyl acrylate; and / or

[0021] b) 0.1 to 4.0% by weight of units derived from vinyltrimethoxysilane.

[0022] The amount can be easily 1 H-NMR was used for detection.

[0023] On the other hand, the glass fiber reinforced polypropylene-based composition can be obtained by compounding glass fibers having a fiber length of 2 to 5 mm (ie, the fiber length is the length before compounding).

[0024] The glass fiber reinforced polypropylene-based composition described herein also generally contains carbon black pigment. The carbon black pigment is mixed in the form of a masterbatch, so that the base polymer described herein is also suitable as a carrier polymer for carbon black.

[0025] Preferably, the glass fiber reinforced polypropylene-based composition according to the present invention comprises a propylene-1-butene random copolymer or an ethylene-propylene random copolymer having a melting temperature of 141 to 148°C.

[0026] Further preferably, the glass fiber reinforced polypropylene-based composition according to the present invention comprises a propylene-1-butene random copolymer, wherein the content of units derived from 1-butene of the propylene-1-butene random copolymer is 4.0 to 6.0 wt%. In addition, even more preferably, the propylene-1-butene random copolymer is the only random propylene copolymer contained in the glass fiber reinforced polypropylene-based composition. Most preferably, the melting temperature of the propylene-1-butene random copolymer having a content of units derived from 1-butene of 4.0 to 6.0 wt% is 141 to 148 ° C.

[0027] In yet another aspect, the glass fiber reinforced polypropylene-based composition described herein has at least two melting points, a first melting point in the range of 95 to 103 °C and a second melting point in the range of 135 to 150 °C.

[0028] Preferably, the glass fiber reinforced polypropylene based composition has a tensile strength of at least 50.0 MPa and at the same time a strain at break of at least 5.0%, as determined in a tensile test performed on injection molded specimens.

[0029] Preferably, the glass fiber reinforced polypropylene-based composition as described herein comprises:

[0030] c) 0.05 to 0.9 wt % of a slip agent relative to the total weight of the glass fiber reinforced polypropylene-based composition, wherein the slip agent is wax-containing erucamide.

[0031] In another aspect, the present invention relates to an article comprising the glass fiber reinforced polypropylene-based composition described herein. Particularly preferably, the glass fiber reinforced polypropylene-based composition is present in an amount of at least 98.0 wt % relative to the total weight of the article. Also preferably, the article is an automotive interior article.

[0032] The present invention also relates to the use of the glass fiber reinforced polypropylene based composition described herein for replacing leather-polymer composite materials. DETAILED DESCRIPTION

[0033] Further preferred aspects are discussed below. The present invention preferably relates to a glass fiber reinforced polypropylene based composition having a melt flow rate (ISO 1133, 2.16 kg; 230°C) of 1.0 to 50 g / 10 min, the glass fiber reinforced polypropylene based composition comprising:

[0034] a) 40 to 55 wt% of a propylene-1-butene random copolymer having:

[0035] aa) a melting temperature of 135 to 150° C. (DSC; ISO 11357-3);

[0036] ab) a content of units derived from 1-butene of 3.0 to 9.0% by weight (determined by NMR spectroscopy);

[0037] ac) a melt flow rate of 8.0 to 120 g / 10 min (ISO 1133, 2.16 kg; 230° C.);

[0038] b) 20 to 40% by weight of a high-pressure polyethylene acrylate copolymer, wherein the density of the high-pressure polyethylene acrylate copolymer is 910 to 935 kg / m 3 , the high pressure polyethylene acrylate copolymer optionally contains units derived from vinyltrimethoxysilane;

[0039] c) 10 to 30% by weight of short glass fibers;

[0040] d) 0.5 to 2.5 wt % of a coupling agent;

[0041] e) 0.05 to 0.9 wt % of a slip agent;

[0042] All amounts are relative to the total weight of the glass fiber reinforced polypropylene based composition.

[0043] The present invention preferably relates to a glass fiber reinforced polypropylene-based composition, wherein the melt flow rate (ISO 1133, 2.16 kg; 230° C.) of the glass fiber reinforced polypropylene-based composition is 1.0 to 50 g / 10 min, and the glass fiber reinforced polypropylene-based composition comprises:

[0044] a) 40 to 55 wt% of a propylene-1-butene random copolymer having:

[0045] aa) a melting temperature of 141 to 148°C (DSC; ISO 11357-3);

[0046] ab) a content of units derived from 1-butene of 4.0 to 6.0% by weight (determined by NMR spectroscopy);

[0047] ac) a melt flow rate of 8.0 to 120 g / 10 min (ISO 1133, 2.16 kg; 230° C.);

[0048] b) 20 to 40% by weight of a high-pressure polyethylene acrylate copolymer, wherein the density of the high-pressure polyethylene acrylate copolymer is 910 to 935 kg / m 3 , the high pressure polyethylene acrylate copolymer optionally contains units derived from vinyltrimethoxysilane;

[0049] c) 10 to 30% by weight of short glass fibers;

[0050] d) 0.5 to 2.5 wt % of a coupling agent;

[0051] e) 0.05 to 0.9 wt % of a slip agent;

[0052] All amounts are relative to the total weight of the glass fiber reinforced polypropylene based composition.

[0053] In another particularly preferred embodiment, the present invention relates to a glass fiber reinforced polypropylene-based composition, wherein the melt flow rate (ISO 1133, 2.16 kg; 230° C.) of the glass fiber reinforced polypropylene-based composition is 1.0 to 50 g / 10 min, and the glass fiber reinforced polypropylene-based composition comprises:

[0054] a) 40 to 55 wt% of a propylene-1-butene random copolymer having:

[0055] aa) a melting temperature of 141 to 148°C (DSC; ISO 11357-3);

[0056] ab) a content of units derived from 1-butene of 4.0 to 6.0% by weight (determined by NMR spectroscopy);

[0057] ac) a melt flow rate of 8.0 to 120 g / 10 min (ISO 1133, 2.16 kg; 230° C.);

[0058] b) 20 to 40% by weight of a high-pressure polyethylene acrylate copolymer, wherein the density of the high-pressure polyethylene acrylate copolymer is 910 to 935 kg / m 3 , the high pressure polyethylene acrylate copolymer contains units derived from vinyltrimethoxysilane;

[0059] c) 10 to 30% by weight of short glass fibers;

[0060] d) 0.5 to 2.5 wt % of a coupling agent;

[0061] e) 0.05 to 0.9 wt % of a slip agent;

[0062] All amounts are relative to the total weight of the glass fiber reinforced polypropylene based composition.

[0063] For this embodiment, the high pressure polyethylene acrylate copolymer preferably contains:

[0064] 7.0 to 12.0 wt. % of units derived from butyl acrylate; and / or

[0065] 0.1 to 4.0 wt. % of units derived from vinyltrimethoxysilane.

[0066] If not stated otherwise, the above particularly preferred embodiments may be combined with other aspects of the present description.

[0067] Short Glass Fiber(GF)

[0068] The average (D 50 ) The fiber length (before compounding) is 1 to 10 mm, preferably 2 to 5 mm. The aspect ratio is preferably 200 to 400, more preferably 250 to 350.

[0069] Coupling agent

[0070] Coupling agents for glass fiber reinforced polyolefins are known in the art and are commercially available. These resins are typically reaction-modified (e.g., grafted) polypropylenes made by reactive extrusion, such as polypropylene grafted with maleic anhydride (PP-g-MAH). Suitable products include Scona TPPP 8112 and Scona TPPP 9112 from Byk-Kometra, Germany.

[0071] Production process and catalyst of propylene-1-butene random copolymer or ethylene-propylene random copolymer (base polymer)

[0072] In order to prepare the propylene-1-butene random copolymer or the ethylene-propylene random copolymer, a specific catalyst system should be used. Such a catalyst system can be obtained by the metallocene catalyst complex and the cocatalyst described below.

[0073] Preferred metallocene catalyst complexes include:

[0074] rac-dimethylsilanediylbis[2-methyl-4-(3',5'-dimethylphenyl)-5-methoxy-6-tert-butylinden-1-yl]zirconium dichloride;

[0075] rac-trans-dimethylsilanediyl[2-methyl-4-(4'-tert-butylphenyl)-inden-1-yl][2-methyl-4-(4'-tert-butylphenyl)-5-methoxy-6-tert-butylinden-1-yl]zirconium dichloride;

[0076] rac-trans-dimethylsilanediyl[2-methyl-4-(4'-tert-butylphenyl)-inden-1-yl][2-methyl-4-phenyl-5-methoxy-6-tert-butylinden-1-yl]zirconium dichloride;

[0077] rac-trans-dimethylsilanediyl[2-methyl-4-(3',5'-tert-butylphenyl)-1,5,6,7-tetrahydro-s-indane-1-yl][2-methyl-4-(3',5'-dimethylphenyl)-5-methoxy-6-tert-butylindane-1-yl]zirconium dichloride;

[0078] rac-trans-dimethylsilanediyl[2-methyl-4,8-bis-(4'-tert-butylphenyl)-1,5,6,7-tetrahydro-s-indan-1-yl][2-methyl-4-(3',5'-dimethylphenyl)-5-methoxy-6-tert-butylindan-1-yl]zirconium dichloride;

[0079] rac-trans-dimethylsilanediyl[2-methyl-4,8-bis-(3',5'-dimethylphenyl)-1,5,6,7-tetrahydro-s-indan-1-yl][2-methyl-4-(3',5'-dimethylphenyl)-5-methoxy-6-tert-butylindan-1-yl]zirconium dichloride; and

[0080] Racemic-trans-dimethylsilanediyl[2-methyl-4,8-bis-(3',5'-dimethylphenyl)-1,5,6,7-tetrahydro-s-indan-1-yl][2-methyl-4-(3',5'-di-tert-butylphenyl)-5-methoxy-6-tert-butylindan-1-yl]zirconium dichloride.

[0081] Particularly preferred is rac-trans-dimethylsilanediyl[2-methyl-4,8-bis-(3',5'-dimethylphenyl)-1,5,6,7-tetrahydro-s-indan-1-yl][2-methyl-4-(3',5'-dimethylphenyl)-5-methoxy-6-tert-butylinden-1-yl]zirconium dichloride.

[0082] Catalyst

[0083] In order to form active catalytic species it is necessary to use a cocatalyst which is well known in the art. According to the present invention a cocatalyst system comprising a boron containing cocatalyst and an aluminoxane cocatalyst is used in combination with the metallocene catalyst complex defined above.

[0084] The aluminoxane cocatalyst may be one of the following formula (I):

[0085]

[0086] In the formula, n is 6 to 20, and R has the following meanings.

[0087] Aluminoxanes are made of organoaluminum compounds (e.g., aluminoxanes of the formula AlR3, AlR2Y, and Al2R3Y3, wherein R can be, for example, C1-C 10 Alkyl (preferably C1-C5 alkyl or C3-C 10 Cycloalkyl), C7-C 12 Arylalkyl or alkylaryl and / or phenyl or naphthyl, wherein Y can be hydrogen, halogen (preferably chlorine or bromine) or C1-C 10 The obtained oxygen-containing aluminoxane is usually not a pure compound but a mixture of oligomers of formula (I).

[0088] The preferred aluminoxane is methylaluminoxane (MAO). Since the aluminoxane used as a cocatalyst in the present invention is not a pure compound due to its preparation method, the molar concentration of the aluminoxane solution hereinafter is based on its aluminum content. In addition, a boron-containing cocatalyst is used in combination with the aluminoxane cocatalyst.

[0089] The catalyst complex desirably comprises a cocatalyst, preferably some boron-containing cocatalyst. Thus, particularly preferred borates for use in the present invention comprise a trityl ion, i.e., a triphenylcarbenium ion. Thus, the use of Ph3CB(PhF5)4 and the like is particularly advantageous.

[0090] The catalyst system of the present invention is used in a supported form. The particulate support material used is silicon dioxide or a mixed oxide (e.g., silicon dioxide-alumina), in particular silicon dioxide. A silicon dioxide support is preferably used. Those skilled in the art know the process required for supporting metallocene catalysts. In a preferred embodiment, the catalyst system corresponds to ICS3 of WO2020 / 239602A1.

[0091] The propylene-1-butene random copolymer or ethylene-propylene random copolymer of the present invention is made by a multistage process. It is highly recommended to use a combination of a loop reactor and a gas phase reactor. Usually, the first reactor will be a loop reactor. Preferably, a combination of a loop reactor-gas phase reactor 1-gas phase reactor 2 is used. In a preferred embodiment, polypropylene 1-butene copolymer is produced in the first loop reactor and the first gas phase reactor. Particularly preferably, a C4 / C3 ratio of 30 to 50 mol / kmol is used in the first loop reactor. Further particularly preferably, a C4 / C3 ratio of 28 to 42 mol / kmol is used in the first gas phase reactor.

[0092] In general, the amount of catalyst used will depend on the nature of the catalyst, the reactor type and conditions, and the desired properties of the polymer product.As is well known in the art, hydrogen can be used to control the molecular weight of the polymer.

[0093] High pressure polyethylene acrylate copolymer

[0094] Density 910 to 935 kg / m 3 High pressure polyethylene acrylate copolymers optionally containing units derived from vinyl trimethoxysilane are commercially available. As described by Jeremic (Polyethylene, in Ullmann's Encyclopedia of Industrial Chemistry, 2014), these copolymers are produced in a tubular or autoclave high pressure process without the use of a catalyst. Copolymers with acrylates (e.g., methyl acrylate (EMA), ethyl acrylate (EEA), butyl acrylate (EBA), and methyl methacrylate (EMMA)) are specifically described in Chapter 2.5 of the above overview. Suitable processes including copolymerization with vinyl trimethoxysilane are described, for example, in EP 1923404 A1, WO 2005 / 023908 A1, and EP 3035344 A1. As described in EP 3035344 A1, it is particularly preferred to use lubricating oil in the compressor. Preferred tubular reactor conditions are a pressure of 2100 to 2600 bar and a temperature of 280 to 320°C.

[0095] Typical commercial and preferred products are Borealis OE4117, Borealis OE4110SI and Borealis OE2125 provided by Borealis AG, Austria. Preferably, the glass fiber reinforced polypropylene-based composition described herein does not include ethylene-vinyl acetate (EVA)-based copolymers.

[0096] additive

[0097] Typical additives are acid scavengers, antioxidants, colorants, light stabilizers, plasticizers, slip agents, anti-scratch agents, dispersants, processing aids, lubricants and pigments.

[0098] Such additives are commercially available and are described, for example, in "Plastic Additives Handbook" by Hans Zweifel, 6th edition, 2009 (pp. 1141 to 1190).

[0099] Furthermore, the term "additive (AD)" according to the present invention also includes support materials, in particular polymeric support materials.

[0100] The amount of the additive is preferably not higher than 5.0 wt %, for example in the range of 0.1 to 4.0 wt %, relative to the glass fiber reinforced polypropylene-based composition.

[0101] Experimental methods

[0102] a) MFR2 is measured according to ISO 1133 (230°C, 2.16 kg load) (230°C for polypropylene polymers; 190°C for polyethylene polymers).

[0103] b) Quantification of microstructure (area defects) by NMR spectroscopy

[0104] Quantitative nuclear magnetic resonance (NMR) spectroscopy was used to quantify the polypropylene copolymers.

[0105] A Bruker Advance III 400 NMR spectrometer was used to analyze the 1 H and 13 C was operated at 400.15 and 100.62 MHz, respectively, to record the quantitative 13 C{ 1 H} NMR spectra. All spectra were obtained using 13 The C-optimized 10 mm extended temperature probe was recorded at 125 °C and all pneumatics were operated using nitrogen.

[0106] About 200 mg of the material was dissolved in 1,2-tetrachloroethane-d2 (TCE-d2). To ensure a homogeneous solution, the NMR tube was further heated in a rotary oven for at least 1 hour after preliminary sample preparation in a heating block. After insertion of the magnet, the tube was rotated at 10 Hz. This setup was chosen primarily to obtain the high resolution required for quantification of the stereoregularity distribution (Busico, V., Cipullo, R., Prog. Polym. Sci. 26 (2001) 443; Busico, V.; Cipullo, R., Monaco, G., Vacatello, M., Segre, AL, Macromolecules 30 (1997) 6251). Standard single pulse excitation was performed using NOE and a double-layer WALTZ16 decoupling scheme (Zhou, Z., Kuemmerle, R., Qiu, X., Redwine, D., Cong, R., Taha, A., Baugh, D. Winniford, B., J. Mag. Reson. 187 (2007) 225; Busico, V., Carbonniere, P., Cipullo, R., Pellecchia, R., Severn, J., Talarico, G., Macromol. Rapid Commun. 2007, 28, 11289). A total of 8192 (8k) transients were collected for each spectrum.

[0107] Using a proprietary computer program, quantitative 13 C{ 1 H}NMR spectra are processed and integrated, and the relevant quantitative properties are determined from the integration.

[0108] For propylene homopolymers, all chemical shifts are internally referenced to the methyl isotactic pentad (mmmm) at 21.85 ppm.

[0109] Characteristic signals corresponding to regio defects (Resconi, L., Cavallo, L., Fait, A., Piemontesi, F., Chem. Rev. 2000, 100, 1253; Wang, WJ., Zhu, S., Macromolecules 33 (2000), 1157; Cheng, HN, Macromolecules 17 (1984), 1950) or comonomers were observed.

[0110] The presence of two methyl sites at 17.7 and 17.2 ppm indicated the presence of a 2,1 erythro regio defect and was confirmed by other characteristic sites. No characteristic signals corresponding to other types of regio defects were observed (Resconi, L., Cavallo, L., Fait, A., Piemontesi, F., Chem. Rev. 2000, 100, 1253).

[0111] The amount of 2,1-erythro regiodefects was quantified using the average integral of two characteristic methyl sites at 17.7 and 17.2 ppm:

[0112] P 21e =(I e6 +I e8 ) / 2

[0113] The amount of 1,2 primary incorporation of propene was quantified based on the methyl region and corrected for sites within this region that are not associated with primary incorporation and for primary incorporation sites outside this region:

[0114] P 12 =I CH3 +P 21e

[0115] The total amount of propene is quantified as the sum of the primary incorporated propene and all other regio defects present:

[0116] P 总 =P 12 +P 21e

[0117] The mole percentage of 2,1-erythro regio defects is quantified relative to all propylene:

[0118] [21e]mol-%=100*(P 21e / P 总 )

[0119] c) Comonomer content of 1-butene in the propylene-1-butene copolymer (P)

[0120] A Bruker Avance III 500 NMR spectrometer was used to analyze the 1 H and 13 The quantitative data in the molten state were recorded at 500.13 and 125.76 MHz respectively. 13 C{ 1 H} NMR spectra. All spectra were obtained using 13C optimized 7 mm magic angle spinning (MAS) probe was recorded at 180 °C, and all pneumatics were operated with nitrogen. Approximately 200 mg of material was loaded into a 7 mm outer diameter zirconium oxide MAS rotor and spun at 4 kHz. This setting was chosen primarily for the high sensitivity required for rapid identification and accurate quantification. (Klimke, K., Parkinson, M., Piel, C., Kaminsky, W., Spiess, H. W., Wilhelm, M., Macromol. Chem. Phys. 2006; 207: 382., Parkinson, M., Klimke, K., Spiess, H. W., Wilhelm, M., Macromol. Chem. Phys. 2007; 208: 2128., Castignolles, P., Graf, R., Parkinson, M., Wilhelm, M., Gaborieau, M., Polymer 50 (2009) 2373). The analytes were characterized by NOE (Klimke, K., Parkinson, M., Piel, C., Kaminsky, W., Spiess, H. W., Wilhelm, M., Macromol. Chem. Phys. 2006; 207: 382., Pollard, M., Klimke, K., Graf, R., Spiess, H. W., Wilhelm, M., Sperber, O., Piel, C., Kaminsky, W., Macromolecules 2004; 37: 813) and RS-HEPT decoupling (Filip, X., Tripon, C., Filip, C., J. Mag. Resn. 2005, 176, 239., Griffin, J. M., Tripon, C., Samoson, A., Filip, C. and Brown, S. P., Mag. Res. in Chem. 2007) with a short recycle delay of 3 s. 45, S1, S198) with standard single pulse excitation. A total of 16384 (16k) transients were acquired for each spectrum.

[0121] right 13 C{ 1 H} NMR spectra were processed and integrated, and the relevant quantitative properties were determined from the integration. All chemical shifts were internally referenced to the methyl isotactic pentad (mmmm) at 21.85 ppm.

[0122] A basic comonomer content method spectroscopic analysis method characteristic signal corresponding to 1-butene incorporation was observed and the comonomer content was quantified as follows.

[0123] The amount of 1-butene incorporated in the PPBPP isolation sequence was quantified using the integral of the αB2 site at 43.6 ppm, which takes into account the number of reported sites for each comonomer:

[0124] B=I α / 2

[0125] The amount of 1-butene incorporated in the PPBBPP bicontinuous sequence was quantified using the integral of the ααB2B2 site at 40.5 ppm, which takes into account the number of reported sites for each comonomer:

[0126] BB=2*I αα

[0127] When bicontinuous incorporation is observed, compensation needs to be made for the amount of 1-butene incorporated in the PPBPP separation sequence due to the overlap of the αB2 and αB2B2 signals at 43.9 ppm:

[0128] B=(I α -2*I αα ) / 2

[0129] The total 1-butene content was calculated based on the sum of separated 1-butene and continuously incorporated 1-butene:

[0130] B 总 =B+BB

[0131] The amount of propylene is quantified based on the major Sαα methylene site at 46.7 ppm and compensated for the relative amounts of αB2 and αB2B2 methylene units of propylene which are not accounted for (note that B and BB count the number of butane monomers per sequence, not the number of sequences):

[0132] P 总 =I Sαα +B+BB / 2

[0133] The total mole fraction of 1-butene in the polymer is then calculated as:

[0134] f B =(B 总 / (B 总 +P 总 )

[0135] The fully integrated equation for the mole fraction of 1-butene in the polymer is:

[0136] f B =(((I α -2*I αα ) / 2)+(2*I αα ))I Sαα +((I α -2*Iαα ) / 2)+((2*I αα ) / 2))+((I α -2*I αα ) / 2)+(2*I αα ))

[0137] Simplified to:

[0138] f B =(Iα / 2+Iαα) / (I Sαα +Iα+I αα )

[0139] The mole percent of total comonomer incorporation for 1-butene is calculated in the conventional manner from the mole fraction:

[0140] B[mol-%]=100*f B

[0141] The weight percent of total comonomer incorporation for 1-butene was calculated from the mole fraction in the standard manner:

[0142] B [weight %] = 100 * (f B *56.11) / ((f B *56.11)+((1-f B )*42.08))

[0143] d) Determination of acrylate and VTMS content in high pressure copolymers

[0144] Fourier transform infrared (FTIR) spectroscopy was used to determine the butyl acrylate (BA) and vinyl trimethoxysilane (VTMS) contents in high pressure polyethylene acrylate copolymers.

[0145] For butyl acrylate (BA), FTIR was performed on compression molded plaques of the polymer to be analyzed and the wavelength was 3450 cm -1 The BA peak at 2020cm -1 The content is calculated by the ratio between the PE peaks at 13 C{ 1 The H} NMR spectra were calibrated in the concentration range of 6 to 27 wt % BA. Alternatively, 13 C{ 1 H}NMR spectroscopy was used to directly determine the BA content. Similar methods can be applied to vinyl acetate and other acrylic esters.

[0146] For vinyltrimethoxysilane (VTMS), FTIR was performed on compression molded plaques of the polymer to be analyzed and the peaks were plotted at 1095 cm -1 The Si-O peak at 2664 cm-1 The content is calculated by the ratio between the PE peaks at 13 C{ 1 Alternatively, the elemental silicon content can be calculated from the X-ray fluorescence (XRF) determination, given that Mw[Si]=28.0855 g / mol and Mw[VTMS]=148.23 g / mol.

[0147] e) Melting temperature T m and crystallization temperature T c

[0148] The melting temperature T was determined by differential scanning calorimetry (DSC) according to ISO 11357-3 using a TA-Instruments 2920 Dual-Cell equipped with an RSC refrigeration unit and a data station. m In the heating / cooling / heating cycle between +23°C and +210°C, a heating rate and a cooling rate of 10°C / min were applied. The crystallization temperature (T c ) is determined by the cooling step, while the melting temperature (T m ) and melting enthalpy (H m ) is determined in the second heating step.

[0149] f) Tensile test

[0150] The tensile modulus, tensile strength and elongation at break were measured at 23°C according to ISO 527-2 (crosshead speed 1 mm / min for tensile modulus and 50 mm / min otherwise) using injection molded specimens (dog 10 bone shape, 4 mm thickness) produced according to EN ISO 1873-2 and molded at 230°C according to ISO 527-2 (1B).

[0151] g) Soft touch

[0152] Soft touch and leather similarity were evaluated by a trained three-person panel.

[0153] Example

[0154] Catalyst preparation:

[0155] The catalysts used in Examples IE1 to IE4 of the present invention were prepared according to the procedure described in WO 2013 / 007650 A1 for catalyst E2, by adjusting the amounts of metallocene and MAO to achieve the Al / Zr ratios shown in Table 1. The catalysts had been prepolymerized offline with propylene according to the procedure described in WO 2013 / 007650 A1 for catalyst E2P.

[0156] The complex used is:

[0157] Racemic-trans-Me2Si(2-Me-4-(p-iBuPh)-lnd)(2-Me-4-Ph-5-OMe-6-iBu-lnd)ZrCl2).

[0158] Offline prepolymerization degree: 3.3g / g

[0159] Al / Zr molar ratio in catalyst: 431 mol / mol

[0160] The metallocene complex content of the off-line prepolymerization catalyst: 0.696 wt%.

[0161] Preparation of a propylene-1-butene random copolymer or an ethylene-propylene random copolymer (base polymer) having a melting temperature (Tm) in the range of 135 to 150° C., a content of units derived from 1-butene in the range of 3.0 to 9.0% by weight, or a content of units derived from ethylene in the range of 2.0 to 6.0% by weight, and a melt flow rate in the range of 8 to 120 g / 10 min.

[0162] The conditions are shown in the following table.

[0163]

[0164] *Visbreaking

[0165] **1,3:2,4-Di(3,4-dimethylbenzylidene)sorbitol

[0166] Examples IE1 to IE4 and CE1 to CE3 were prepared by compounding on a co-rotating twin screw extruder with a screw configuration typical for glass fiber compounding, using a temperature range of 200 to 240° C. Compounding formulations of the compositions.

[0167]

[0168]

[0169]

[0170] As shown in the table below, the composition has the following properties / parameters:

[0171]

[0172] It can be seen that the elongation at break of comparative example CE3, which does not contain a high pressure polyethylene acrylate copolymer, is not high enough. The elongation at break of comparative example CE2, which does not contain a coupling agent, is even lower. Comparative example CE1 has a good elongation at break, but a low tensile strength, while all examples IE1 to IE4 have acceptable tensile strength values ​​above 50.0 MPa and at the same time an elongation at break of at least 5.0%. The composition containing a propylene-1-butene random copolymer surprisingly exhibits better stiffness.

Claims

1. A glass fiber reinforced polypropylene-based composition, wherein the melt flow rate (ISO 1133, 2.16 kg; 230° C.) of the glass fiber reinforced polypropylene-based composition is 1.0 to 50 g / 10 min, and the glass fiber reinforced polypropylene-based composition comprises: a) 40 to 55% by weight of a propylene-1-butene random copolymer or an ethylene-propylene random copolymer, wherein the propylene-1-butene random copolymer or the ethylene-propylene random copolymer has: aa) a melting temperature of 135 to 150° C. (DSC; ISO 11357-3); ab) a content of units derived from 1-butene of 3.0 to 9.0% by weight or a content of units derived from ethylene of 2.0 to 6.0% by weight (determined by NMR spectroscopy); ac) a melt flow rate of 8.0 to 120 g / 10 min (ISO 1133, 2.16 kg; 230° C.); b) 20 to 40% by weight of a high-pressure polyethylene acrylate copolymer, wherein the density of the high-pressure polyethylene acrylate copolymer is 910 to 935 kg / m 3 , the high pressure polyethylene acrylate copolymer optionally contains units derived from vinyltrimethoxysilane; c) 10 to 30% by weight of short glass fibers; d) 0.5 to 2.5 wt % of a coupling agent; All amounts are relative to the total weight of the glass fiber reinforced polypropylene based composition.

2. The glass fiber reinforced polypropylene-based composition according to claim 1, wherein: The glass fiber reinforced polypropylene-based composition further comprises: e) 0.05 to 0.9 wt% of a slip agent relative to the total weight of the glass fiber reinforced polypropylene-based composition.

3. The glass fiber reinforced polypropylene-based composition according to claim 1 or 2, wherein: The high pressure polyethylene acrylate copolymer contains units derived from butyl acrylate.

4. The glass fiber reinforced polypropylene based composition according to any one of the preceding claims, wherein: The high pressure polyethylene acrylate copolymer contains units derived from vinyltrimethoxysilane.

5. The glass fiber reinforced polypropylene based composition according to any one of the preceding claims, wherein: The high pressure polyethylene acrylate copolymer contains: 7.0 to 12.0 wt. % of units derived from butyl acrylate; and / or 0.1 to 4.0 wt. % of units derived from vinyltrimethoxysilane.

6. The glass fiber reinforced polypropylene based composition according to any one of the preceding claims, wherein: The glass fiber reinforced polypropylene-based composition can be prepared by compounding the average fiber length (D 50 ) is obtained by glass fibers with a diameter of 2 to 5 mm.

7. A glass fiber reinforced polypropylene based composition according to any one of the preceding claims, wherein: The glass fiber reinforced polypropylene-based composition contains carbon black pigment.

8. The glass fiber reinforced polypropylene based composition according to any one of the preceding claims, wherein: The propylene-1-butene random copolymer or the ethylene-propylene random copolymer has a melting temperature (DSC; ISO 11357-3) of 141 to 148°C.

9. The glass fiber reinforced polypropylene based composition according to any one of the preceding claims, wherein: The glass fiber reinforced polypropylene-based composition comprises 40 to 50 wt% of a propylene-1-butene random copolymer as the only random copolymer, and preferably, the propylene-1-butene random copolymer has a content of units derived from 1-butene of 4.0 to 6.0 wt%.

10. The glass fiber reinforced polypropylene based composition according to any one of the preceding claims, wherein: The composition has at least two melting points, a first melting point in the range of 95 to 103° C. and a second melting point in the range of 135 to 150° C. (DSC; ISO 11357-3).

11. A glass fiber reinforced polypropylene based composition according to any one of the preceding claims, wherein: The glass fiber reinforced polypropylene-based composition has a tensile strength of at least 50.0 MPa and an elongation at break of at least 5% measured according to ISO 527-2 (crosshead speed for tensile modulus is 1 mm / min, crosshead speed for others is 50 mm / min) using injection molded test specimens (dog 10 bone shape, 4 mm thickness) produced according to EN ISO 1873-2 and molded according to ISO 527-2 (1B) at 230°C.

12. The glass fiber reinforced polypropylene based composition according to any one of the preceding claims, wherein: The glass fiber reinforced polypropylene-based composition comprises: e) 0.05 to 0.9 wt % of a slip agent relative to the total weight of the glass fiber reinforced polypropylene-based composition, wherein the slip agent is erucamide containing wax.

13. An article comprising the glass fiber reinforced polypropylene-based composition according to any one of claims 1 to 12, wherein: Preferably, the glass fiber reinforced polypropylene-based composition is present in an amount of at least 98.0 wt % relative to the total weight of the article.

14. The article according to claim 13, wherein The product is an automobile interior decoration product.

15. Use of the glass fiber reinforced polypropylene based composition according to any one of claims 1 to 12 for replacing leather-polymer composite materials.

Citation Information

Patent Citations

  • Method for preparing an ethylene-silane copolymer

    EP1923404A1

  • High pressure radical polymerisation process for a copolymer of ethylene with silane groups containing comonomer

    EP3035344A1

  • Polypropylene composite

    EP3105287A1

  • Crosslinkable high pressure polyethylene composition, a process for the preparation thereof, a pipe and a cable prepared thereof

    WO2005023908A1

  • catalysts

    WO2013007650A1